Static magnetic field treatment enhanced photosynthetic performance in soybean under supplemental ultraviolet-B radiation - Kataria, Sunita; Jain, Meeta; Rastogi, Anshu; Brestic, Marian (Photosynthesis research, 2021)
The study was performed to analyze the impact of seed pretreatment by static magnetic field (SMF) of 200 mT for 1 h on photosynthetic performance of soybean (Glycine max) seedlings under ambient (aUV-B) and supplemental ultraviolet-B (a+sUV-B) stress. Ambient and supplemental UV-B were found to decrease the plant growth, chlorophyll concentration, PSII efficiency, selected JIP-test parameters such as Fv/Fm, φEo, ΔV(I-P), PIABS, PItotal, and rate of photosynthesis in the leaves of soybean seedlings emerged from untreated (UT) seeds. aUV-B and a+sUV-B were observed to increase the synthesis of UV-B-absorbing substances (UAS), reactive oxygen species (ROS) like superoxide radical (O2·-) and hydrogen peroxide (H2O2), antioxidants like ascorbic acid and α-tocopherol and decrease the nitrate reductase (NR) activity; subsequently, it results in a decreased rate of photosynthesis, biomass accumulation, and yield. However, our results provided evidence that SMF pretreatment increased the tolerance of soybean seedlings to UV-B radiation by increased NO content and NR activity; higher efficiency of PSII, higher values of φEo, ΔV(I-P), PIABS, and PItotal, decreased intercellular CO2 concentration, lower amount of UAS, ROS, and antioxidants that consequently improve the yield of soybean plants under aUV-B as well as a+sUV-B stress. Thus, our results suggested that SMF pretreatment mitigates the adverse effects of UV-B stress by the enhancement in photosynthetic performance along with higher NO content which may be able to protect the plants from the deleterious effects of oxidative stress caused by UV-B irradiation.
Keywords: Photosynthesis; Chlorophyll; Plant Leaves; Chl fluorescence; Glycine max; Nitric oxide; semenáček; chlorofyl; magnetické pole; Growth; ultrafialové záření; listy rostlin; UV-B; peroxid vodíku; Seedlings; PSII efficiency; Ultraviolet Rays; Magnetic Fields; fotosyntéza; Hydrogen Peroxide